1999
DOI: 10.1097/00000539-199907000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Transesophageal Echocardiography to Guide Central Venous Catheter Placement in Congenital Heart Surgery Patients

Abstract: Transesophageal echocardiography can be used to guide central venous catheter placement in congenital heart surgery. Central venous catheters that seem to be located high in the right atrium by chest radiograph in these patients are often actually in the superior vena cava and pose little risk of cardiac perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…[1] Ultrasound has reduced some of the complications during its insertion, but cannot locate the catheter tip in relation to heart. Only transesophageal echocardiography can accurately detect a CVC tip in relation to superior vena cava (SVC) and right atrium (RA),[23] but its availability as a bedside tool is limited to major hospitals. In our centre, we routinely perform a post-procedure chest X-ray (CXR) to confirm the tip of the catheter and we could detect some of the catheter malpositions that are illustrated below.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Ultrasound has reduced some of the complications during its insertion, but cannot locate the catheter tip in relation to heart. Only transesophageal echocardiography can accurately detect a CVC tip in relation to superior vena cava (SVC) and right atrium (RA),[23] but its availability as a bedside tool is limited to major hospitals. In our centre, we routinely perform a post-procedure chest X-ray (CXR) to confirm the tip of the catheter and we could detect some of the catheter malpositions that are illustrated below.…”
Section: Introductionmentioning
confidence: 99%
“…Various landmarks,[23] simple formulae[45] and sophisticated techniques like right atrial ECG[67] and transesophageal echocardiography[78] have been developed to ensure correct placement of the CVC tip. Peres' utilized the patient's height to predict the optimal length of the catheter to be inserted by different approaches and demonstrated that 24% terminated in right atrium.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Transesophageal echocardiography can be used to guide central venous catheter placement in congenital heart surgery. 8 The presence of intracardiac shunting with a VSD cannot be demonstrated in all affected children by 2D-echocardiography. In a recent study, 77 patients, age one day to 15.5 yr were identified over a two year period as having VSDs by colour-flow Doppler (CFD) mapping; 97 defects were noted by colour-flow imaging that were not visualized by standard 2D-echocardiography.…”
Section: Discussionmentioning
confidence: 97%